2019
DOI: 10.1186/s40246-019-0232-4
|View full text |Cite
|
Sign up to set email alerts
|

Three miRNAs cooperate with host genes involved in human cardiovascular disease

Abstract: Background Understanding the roles of miRNAs in cardiovascular disease remains a challenge. Genomic linkage indicates a functional relationship between intronic miRNAs and their host genes. However, few studies have shown functional association between intronic miRNAs and their host coding genes that are genetically associated with cardiovascular disease. Methods In this study, we investigated functional relationship between three protein-coding genes genetically associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…In contrast, hsa-miR-3182 was markedly up-regulated in HP-EC-EVs. A recent research showed that hsa-miR-3182 and its host coding genes are genetically associated with cardiovascular disease [ 27 ], which supported our findings. Our analysis demonstrated that those target mRNAs for hsa-miR-3182 included NOD2, ZCCHC14, DMTF1, STAM2, SLC22A25, AOAH, KIAA1109, HECTD4, SOGA3, RBM47, ADGRL3, PTPRT, KIAA0408, SLC16A7, PSTPIP1.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, hsa-miR-3182 was markedly up-regulated in HP-EC-EVs. A recent research showed that hsa-miR-3182 and its host coding genes are genetically associated with cardiovascular disease [ 27 ], which supported our findings. Our analysis demonstrated that those target mRNAs for hsa-miR-3182 included NOD2, ZCCHC14, DMTF1, STAM2, SLC22A25, AOAH, KIAA1109, HECTD4, SOGA3, RBM47, ADGRL3, PTPRT, KIAA0408, SLC16A7, PSTPIP1.…”
Section: Discussionsupporting
confidence: 91%
“…The copyright holder for this this version posted December 2, 2020. ; https://doi.org/10.1101/2020.12.01.405910 doi: bioRxiv preprint 48 . The embedded miRNAs are often co-expressed with their host genes and can regulate their expression and activity 48,[59][60][61][62] , which support functional relations between the miRNA host-gene, target genes, and biological activity 63,64 . Indeed, we found that twelve of the identified dysregulated miRNAs were embedded in seven host genes that are known to be dysregulated in DMD models and patients (Supplemental table 7).…”
Section: Differentially Expressed Plasmatic Mirnas In Dmd Patientsmentioning
confidence: 96%
“…Increased circulatory levels of hsa-miR-941 were significantly correlated with atherosclerosis risk factors in patients with homozygous familial hypercholesterolemia [ 84 ] and were proposed as a biomarker of ST-segment elevation myocardial infarction [ 85 ]. Other miRNAs associated with claudication distance are also related to cardiac events: hsa-miR-3182 is a regulator of genes involved in angiogenesis and cardiac muscle cell contraction [ 86 ], and increased miR-32-3p circulatory levels have been proposed as a biomarker of severe coronary artery disease [ 87 ] and acute ischemic stroke [ 88 ]. MiR-32-3p also inhibits ER stress-induced cell apoptosis, increasing atherosclerotic plaque stability [ 89 ].…”
Section: Discussionmentioning
confidence: 99%